Application of Magneto-optical Characteristic in Liquid: Verdet Constant as Quality Indicator of Repeatedly Cooking Oil - Sari, Silfiana Puspita; Misto, Misto; Purwandari, Endhah (BERKALA SAINSTEK, 2021)
The Faraday Effect is a magnetooptical phenomenon in physics describing the interaction of light and magnetic fields in a medium. A parameter that indicates the interaction is the Verdet constant. In this research, Verdet constant was measured on cooking oil that has been used several times. Magneto-optical properties were measured using the polarimetry method, which uses a He-Ne Laser beam with a magnetic field treatment of 50 gauss, 80 gauss and 100 gauss. The samples analyzed were bulk and non-bulk cooking oil. Repeated use of cooking oil causes a change in the polarization axis of the polarized laser. This has an impact on the Verdet constant of the material. The difference in the Verdet constant shows that the Verdet constant can be used as an indicator of cooking oil that has been used up to three times.